The philosophical curriculum in Chile and the development of complex thought and metacognition - Vallejos Gómez, Rosse Marie (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
Under a qualitative-interpretive paradigm, a content analysis of the Chilean philosophy plans and programs was carried out, regarding the ministerial guidelines on the development of complex thinking and metacognition contained in them. Based on the categories that emerged, interviews were carried out with the teachers of the level, to compare the consistency of the guidelines with the conceptions and practices described by them. The existence of an academic-rationalist approach to curricular conceptions and activities, reductionist conceptions of complex thought and metacognition, transferring the responsibility of the lack of achievement to their students was verified.